MULTIPLE EYELID LUMPS IN INFANT WITH DYSLIPIDEMIA IN RESOURCE-LIMITED SETTING ANAMBAS ARCHIPELAGO DISTRICT - Febrianti, Santi (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2023)
Objective: Present a case of recurrent multiple eyelid lumps in the infant with dyslipidemia in the limited resources area.  Case Report: A case report on a three-year-old child who had several painless red tumors in his eyelids and was well-nourished. The patient had a similar complaint three times in the last seven months in different sites. No history of atopy, chronic blepharitis, trauma, or eyelid surgery. Laboratory findings showed elevated levels of cholesterol. Warm compresses, antibiotic topical, and erythromycin 50 mg/kgbw/day divided into three doses were the patient's initial therapeutic interventions. For managing dyslipidemia we planned to modification of lifestyle, diet, and activities for two weeks, then evaluate the level of cholesterol. We evaluated and educated the patient’s parent to refer him to an ophthalmologist for further management. However, we had difficulty referring patients to the provincial hospital with an ophthalmologist due to the islands’ geographical location, infrequent and weather-affected transportation, as well as family economics.  Discussions: A hordeolum is a common inflammation of the eyelid margin. Recurrence of hordeolum is usually associated with underlying causes such as systemic disease. Dyslipidemia leads to hypersecretion of meibum which will cause highly concentrated meibum in Meibomian glands, that leads to blockage of ducts of Meibomian glands and Meibomian gland dysfunction (MGD). Initial treatment of hordeolum is indeed conservative, typically limited to the application of warm compresses several times a day and topical antibiotics.  Conclusions: Dyslipidemia is usually associated with recurrent hordeolum. The management of hordeolum is conservative.